Self-awareness in traumatically brain injured (TBI) persons regarding their post-accident abilities - Wootton, Michelle Frances (My University, 2014)
South Africa has the highest global fatality rate per 100 000 which annually leaves thousands dead and even greater numbers severely impaired following motor vehicle accidents. A large percentage of these persons sustain a Traumatic Brain Injury (TBI). Regardless of whether decreased insight following TBI has neurological or psychological aetiology, TBI is believed to hinder rehabilitation efforts in that TBI individuals are unaware of their deficits and the need for rehabilitation. The aims of this study were to determine if self-awareness in severely TBI persons differed markedly from their significant others' perception of their abilities. Furthermore a control group established awarenes'i levels in the general population. Degree of insight was appraised by examining the disagreement between participant and significant other on both the Patient Competency Rating Scale (PCRS) Questionnaire and a modified Draw-A-Person Test. Statistical discordance was found to exist between participant and significant other for only two PCRS items, pointing to sound self-awareness amongst the experimental group. Although TBI persons were more likely to generally over-estimate their abilities, similar relationships were found to exist between participants and significant others in both groups. Few differences were found to exist between the way participants and their significant other visually portrayed them, although statistically significant intergroup differences were found to exist in this mode. These suggested a high level of visual selfawareness in the experimental group, and a tendency for both TBI participants and their significant others to portray participants in markedly different ways from control participants. The unexpectedly high concordance suggests the effectiveness of therapy in improving die self-awareness of TBI persons.